THE EFFECTIVENESS OF COMPLEMENTARY NURSING "WET CUPPING" ON TOTAL CHOLESTEROL IN HYPERTENSION PATIENTS - Latifin, Khoirul; Purwanto, Sigit; Wahyuni, Dian (Journal of Nursing Care and Biomoleculer, 2020)
Introduction: Cardiovascular disease is commonly found in patients with hypertensive disorders. Hypertension has a high risk of causing the new cardiovascular diseases. High cholesterol levels in a person can increase the blood pressure. This study aims to determine the effectiveness of complementary nursing "Wet Cupping" on cholesterol levels in hypertensive patients. Method: This study used an experimental research method with a pre-experimental design, namely one group pretest and posttest design. Respondents were selected using a purposive sampling technique, based on established inclusion criteria, amounting to 16 respondents. Respondents received complementary wet cupping treatments three times in three weeks. The research instruments were standard operating procedures and observation sheets. Result and Analysis: The results of this study indicate that there is a less significant effect on total cholesterol in hypertensive patients after being given complementary wet cupping treatment with a significant value of 0.255 or p-value> 0.05. Although the results of statistical tests did not show significant results, there were 50% of respondents who experienced a decrease in total cholesterol. Discussion: Wet cupping is a prophetic treatment method that has benefits and it does not cause the bad side effects. So that this wet cupping can be a recommendation for people with hypertension to control total cholesterol levels by undergoing regular cupping.